Development and Evaluation of In-Vitro-In-Vivo Correlation (IVIVC) for Capecitabine-Loaded Solid Lipid Nanoparticles - Jana, Mayukh; Patro, Chandra Sekhar; Debnath, Biplab; Banerjee, Sipra Sarkar (Journal of Neonatal Surgery, 2025)
The present study aimed to establish a robust in-vitro-in-vivo correlation (IVIVC) for capecitabine-loaded solid lipid nanoparticles (CPB-SLNs) to predict oral bioavailability and support formulation development. CPB-SLNs were prepared using the modified nanoprecipitation technique and characterized for particle size, entrapment efficiency, zeta potential, drug release, and morphology. In-vitro drug release studies were conducted in phosphate buffer (pH 6.8) to simulate intestinal conditions. In-vivo pharmacokinetic studies were performed in Wistar rats to evaluate drug absorption and systemic availability following oral administration. The in-vitro dissolution profile exhibited sustained release of Capecitabine over 24 hours. At the same time, in-vivo studies demonstrated prolonged plasma retention, extended half-life, and delayed Tmax for CPB-SLNs compared to pure drug suspension. A Level of IVIVC model was established using the Wagner-Nelson method to calculate the fraction of drug absorbed. A strong linear correlation (R² = 0.97) was observed between the cumulative percentage of drug released in-vitro and the fraction absorbed in-vivo. This indicates the feasibility of using in-vitro data to predict in-vivo behavior. The successful establishment of a level IVIVC model confirms that CPB-SLNs provide a reliable and predictable delivery system for oral capecitabine, offering improved pharmacokinetic performance and the potential for dose optimization. This correlation supports further development of CPB-SLNs for clinical application in oral chemotherapy.